Treatment sequencing in metastatic colorectal cancer. (March 2019) - Modest, D.P.; Pant, S.; Sartore-Bianchi, A.
Abstract: Metastatic colorectal cancer (mCRC) remains incurable in most cases, but survival has improved with advances in cytotoxic chemotherapy and targeted agents. However, the optimal use and sequencing of these agents across multiple lines of treatment is unclear. Here, we review current treatment approaches and optimal treatment sequencing across the first-, second- and third-line settings in mCRC, including biological aspects affecting sequencing and rechallenge. Effective first-line therapy is a key determinant of treatment outcomes and should be selected after considering both clinical factors and biological markers, notably RAS and BRAF . The second-line regimen choice depends on the systemic therapies given in first-line. Anti-angiogenic agents (e.g. bevacizumab, ramucirumab and aflibercept) are indicated for most patients, whereas epidermal growth factor receptor (EGFR) inhibitors do not improve survival in the second-line setting. Molecular profiling is important in third-line treatment, with options in RAS wild-type patients including EGFR inhibitors (cetuximab or panitumumab), regorafenib and trifluridine/tipiracil. Immunotherapy with pembrolizumab or nivolumab ± ipilimumab may be considered for patients with high microsatellite instability disease. Targeting HER2/neu amplification shows promise for the subset of CRC tumours displaying this abnormality. Sequencing decisions are complicated by the potential for any treatment break or de-escalation to evoke a distinct clinical progression type. Ongoing trials are investigating the optimal sequencing and timing of therapies for mCRC. Molecular profiling has established new targets, and increasing knowledge of tumour evolution under drug pressure will possibly impact on sequencing. Highlights: Optimal sequencing of cytotoxic/targeted agents in metastatic colorectal cancer remains unclear. First-line choice of therapy is critical as it affects treatment decisions in later lines. Molecular profiling has established new targets that may impact sequencing. Recent knowledge of tumour evolution also has clinical implications for sequencing.